DIGITAL STORYTELLING ENGAGES EFL SECONDARY STUDENTS IN LEARNING READING - Syafira Rahmawati; Muhammad Reza Pahlevi; Kelik Wachyudi (IKIP Siliwangi, 2023)
The primary focus of this research is to examine the level of involvement exhibited by secondary students studying English as a Foreign Language (EFL) in the process of learning reading, specifically through the utilization of Digital Storytelling (DST). This study employs a qualitative research methodology, specifically utilizing a descriptive case study design. Data collection in this research includes the utilization of observations and interviews. The present study employs thematic analysis as stated by Braun and Clarke (2006). The research findings indicate that the implementation of DST has a positive impact on students' reading comprehension, critical thinking abilities, and technological proficiency. Furthermore, fosters increased cognitive, behavioral, and emotional engagement among students. Presentation sessions facilitate interactive discussions, thereby promoting cognitive engagement. The act of developing storyboards and disseminating digital narratives elicits pleasurable and emotionally immersive educational encounters. The research findings illustrate the favorable influence of DST on students' motivation and interest in reading, indicating a heightened emotional involvement in the educational experience.